The Characterization of the Caenorhabditis elegans Mitochondrial Thioredoxin System Uncovers an Unexpected Protective Role of Thioredoxin Reductase 2 in β-Amyloid Peptide Toxicity - Cacho-Valadez, Briseida (Mary Ann Liebert, Inc., 2012)
Aim: Functional in vivo studies on the mitochondrial thioredoxin system are hampered by the embryonic or larval lethal phenotypes displayed by murine or Drosophila knock-out models. Thus, the access to alternative metazoan knock-out models for the mitochondrial thioredoxin system is of critical importance. Results: We report here the characterization of the mitochondrial thioredoxin system of Caenorhabditis elegans that is composed of the genes trx-2 and trxr-2. We demonstrate that the proteins thioredoxin 2 (TRX-2) and thioredoxin reductase 2 (TRXR-2) localize to the mitochondria of several cells and tissues of the nematode and that trx-2 and trxr-2 are upregulated upon induction of the mitochondrial unfolded protein response. Surprisingly, C. elegans trx-2 (lof ) and trxr-2 (null) single and double mutants are viable and display similar growth rates as wild-type controls. Moreover, the lack of the mitochondrial thioredoxin system does not affect longevity, reactive oxygen species production or the apoptotic program. Interestingly, we found a protective role of TRXR-2 in a transgenic nematode model of Alzheimer's disease (AD) that expresses human β-amyloid peptide and causes an age-dependent progressive paralysis. Hence, trxr-2 downregulation enhanced the paralysis phenotype, while a strong decrease of β-amyloid peptide and amyloid deposits occurred when TRXR-2 was overexpressed. Innovation: C. elegans provides the first viable metazoan knock-out model for the mitochondrial thioredoxin system and identifies a novel role of this system in β-amyloid peptide toxicity and AD. Conclusion: The nematode strains characterized in this work make C. elegans an ideal model organism to study the pathophysiology of the mitochondrial thioredoxin system at the level of a complete organism. Antioxid. Redox Signal. 16, 1384–1400.